Upaya Modin Desa Dalam Memberikan Pendidikan Moderasi Beragama Kepada Masyarakat Di Desa Jatirejo - Albab, Ulil; Ahadiyah, Wahyu; Ariska, Mega (Universitas Majalengka, 2024)
The diversity of Indonesian society is one of the most valuable riches, but it can also be a challenge. Multiculturalism in Indonesia does not only include differences in ethnicity, language, and religion, but also the way of life and values ​​held by each group. The purpose of this study was to explore the efforts of village modins in providing religious moderation education to the community in Jatirejo Village, Tikung, Lamongan. The method used in this study was direct data collection in the field using several data collection techniques, including observation, documentation, and interviews with related parties. The results of this study indicate that the efforts of village modins in providing religious moderation education to the community are one way to prevent social conflict caused by differences in religion and belief. By providing education in accordance with the principles of moderation, it is hoped that the community can be more tolerant of differences in religion and belief that exist in society.